Compact Eight-Element MIMO Antenna for UWB Applications - Saurabh A.K.; Srivastava S.K.; Meshram M.K. (My University, 2025)
A compact, low-profile eight-element UWB-MIMO antenna is presented in this investigation. The proposed eight-element MIMO antenna is configured by placing symmetrically orthogonally two identical same-oriented antenna elements on an octagonal-shaped substrate board, which are fed through the tapered microstrip line. A combination of ground stubs is utilized between a pair of antenna elements for better matching and low correlation simultaneously. The proposed MIMO antenna obtained a -10 dB impedance bandwidth (Sij ϵ i=j) of 3.05-15.05 GHz (132.59%) and a minimum isolation value (Sij ϵ i≠j) of 15 dB. The peak gain and total efficiency values are 7.3 dBi and 68.2-88.7%, respectively, in the respective ultra-wideband. Also, the value of ECC is less than 0.15. The performance of the proposed MIMO antenna is found satisfactory, which may be appropriate for UWB application-based user devices. © 2022 IEEE.